A Newly Emergent Turkey Arthritis Reovirus Shows Dominant Enteric Tropism and Induces Significantly Elevated Innate Antiviral and T Helper-1 Cytokine Responses. - Tamer A Sharafeldin; Sunil K Mor; Nader M Sobhy; Zheng Xing; Kent M Reed; Sagar M Goyal; Robert E Porter (PLoS ONE, 2015)
Newly emergent turkey arthritis reoviruses (TARV) were isolated from tendons of lame 15-week-old tom turkeys that occasionally had ruptured leg tendons. Experimentally, these TARVs induced remarkable tenosynovitis in gastrocnemius tendons of turkey poults. The current study aimed to characterize the location and the extent of virus replication as well as the cytokine response induced by TARV during the first two weeks of infection. One-week-old male turkeys were inoculated orally with TARV (O'Neil strain). Copy numbers of viral genes were estimated in intestines, internal organs and tendons at ½, 1, 2, 3, 4, 7, 14 days Post inoculation (dpi). Cytokine profile was measured in intestines, spleen and leg tendons at 0, 4, 7 and 14 dpi. Viral copy number peaked in jejunum, cecum and bursa of Fabricius at 4 dpi. Copy numbers increased dramatically in leg tendons at 7 and 14 dpi while minimal copies were detected in internal organs and blood during the same period. Virus was detected in cloacal swabs at 1-2 dpi, and peaked at 14 dpi indicating enterotropism of the virus and its early shedding in feces. Elevation of IFN-α and IFN-β was observed in intestines at 7 dpi as well as a prominent T helper-1 response (IFN-γ) at 7 and 14 dpi. IFN-γ and IL-6 were elevated in gastrocnemius tendons at 14 dpi. Elevation of antiviral cytokines in intestines occurred at 7dpi when a significant decline of viral replication in intestines was observed. T helper-1 response in intestines and leg tendons was the dominant T-helper response. These results suggest the possible correlation between viral replication and cytokine response in early infection of TARV in turkeys. Our findings provide novel insights which help elucidate viral pathogenesis in turkey tendons infected with TARV.